Dampak Surat Edaran Mahkamah Agung Nomor 3 Tahun 2023 terhadap Kepailitan - Ainia Fitria Rusdi; Mubaroq, Ahmad Muhajir Firrizqi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
The issuance of Supreme Court Circular Letter No. 3 of 2023 has significant implications for the application of the principle of simplified evidence in bankruptcy law, particularly in cases involving apartment and/or low-rise housing developers. This SEMA affirms that bankruptcy petitions against developers generally do not meet the qualifications for the principle of simple proof as stipulated in Article 8(4) of Law No. 37 of 2004, thereby limiting consumers’ access to bankruptcy mechanisms as a means of rapid and effective rights recovery. This study employs a normative legal method with a legislative and conceptual approach to examine the legitimacy of the SEMA within the hierarchy of legal norms and its impact on the balance of civil liability in the tripartite relationship between consumers, developers, and banks under the Apartment Ownership Loan scheme. The research findings indicate that SEMA, as a judicial administrative instrument, lacks the normative standing to limit or deviate from laws, thereby potentially conflicting with the principle of the hierarchy of legislation. This limitation creates an imbalance in civil liability because consumers lose effective legal protection, while developers gain greater protection and banks remain protected as separate creditors. Therefore, the revocation of the relevant provisions is necessary to ensure legal certainty, consumer protection, and the proportionality of the parties’ liabilities.